Comparison of Alpha-Blockers and Antimuscarinics in Improving Ureteral Stent-Related Symptoms: A Meta-Analysis - Gao, Yiyang; Liang, Hengrui; Liu, Luhao; Gurioli, Alberto; Wu, Wenqi (Urology Journal, 2019)
Purpose: A meta-analysiswas conducted to compare alpha-blocker (AB) and antimuscarinic (AM) monotherapies in releasing US-related symptoms. Methods: A comprehensive literature search was performed on online databases PubMed, Web of Science, Medline, and Cochrane library. Ureteric Symptom Score Questionnaire (USSQ), International Prostate Symptom Score (IPSS), quality of life (QoL) and visual analogue pain scale (VAPS) were pooled and compared. Results: Nine full-text articles met the inclusion criteria and have been included. The studies were conducted in 9 different centers between 2009 and 2016. All articles were RCT studies and a total of 654 patients were recorded totally, among which 323 were given alpha-blockers while others were given antimuscarinics. Although patients using alpha-blockers presented lower USSQ scores, no statistically significant difference was recorded in urinary symptom(SMD 0.5, 95 % CI -0.2 to 1.20, P = 0.159), pain(SMD 0.33, 95 % CI -0.26 to 0.92, P = 0.280),general health, work performance(SMD-0.34, 95 % CI -0.08 to 0.76, P = 0.115) and sexual performance (all p > 0.05) (SMD 0.12, 95 % CI -0.10 to 0.34, P = 0.280). Meanwhile IPSS (SMD -0.10, 95 % CI -0.32 to 0.11, P = 0.358), QoL(SMD-0.03, 95 % CI -0.23 to 0.18, P = 0.802) and VAPS(SMD 0.08, 95 % CI -0.15 to 0.31, P = 0.447) were similar between the two groups (all P > 0.05). Conclusion: The analysis suggests that AB showed a similar effect with AM. It is necessary to conduct a larger and more detailed cohort study and find the population that potentially might benefit most by AM.